A Narrative Literature Review on the Use of Augmented Reality in Logistics: Enhancing Training and Operational Efficiency - Budiyanto, Albert; Muslim, Muhammad (Sinergi International Journal of Logistics, 2024)
This study explores the implementation of Augmented Reality (AR) in logistics training and operations, focusing on its effectiveness in improving technical skills, operational efficiency, and user engagement. The review analyzes peer-reviewed literature from major academic databases, using systematic search strategies with defined keywords and inclusion criteria. Key findings show that AR-based training significantly enhances conceptual understanding, reduces task completion times, and increases learner satisfaction. In logistics operations, AR contributes to improved order picking, warehouse mapping, and real-time inventory control, leading to productivity gains and cost reductions. These benefits, however, are context-dependent and influenced by systemic factors such as infrastructure maturity, workforce readiness, organizational culture, and regulatory support. The discussion emphasizes the need for integrated human-centric design, supportive policy frameworks, and targeted investment to overcome barriers to AR adoption. Practical strategies, including the use of proven AR platforms, public-private educational partnerships, and localized pilot implementations, are recommended to facilitate scalable and effective AR integration. Despite promising results, gaps remain in empirical field research and interdisciplinary perspectives, especially in low- and middle-income settings. The review concludes by underscoring the urgency of digital transformation in logistics and the central role of AR in equipping the workforce with future-ready capabilities. Strategic adoption of AR offers a pathway toward more adaptive, efficient, and resilient logistics systems.